Polystyrene chain growth initiated from dialkylzinc for synthesis of polyolefin-polystyrene block copolymers - Kim, Tae Jin; Baek, Jun Won; Moon, Seung Hyun; Lee, Hyun Ju; Park, Kyung Lee; Bae, Sung Moon; Lee, Jong Chul; Lee, Pyung Cheon; Lee, Bun Yeoul (Polymers, 2020)
Polyolefins (POs) are the most abundant polymers. However, synthesis of PO-based block copolymers has only rarely been achieved. We aimed to synthesize various PO-based block copolymers by coordinative chain transfer polymerization (CCTP) followed by anionic polymerization in one-pot via conversion of the CCTP product (polyolefinyl)2Zn to polyolefinyl-Li. The addition of 2 equiv t-BuLi to (1-octyl)2Zn (a model compound of (polyolefinyl)2Zn) and selective removal or decomposition of (tBu)2Zn by evacuation or heating at 130 °C afforded 1-octyl-Li. Attempts to convert (polyolefinyl)2Zn to polyolefinyl-Li were unsuccessful. However, polystyrene (PS) chains were efficiently grown from (polyolefinyl)2Zn; the addition of styrene monomers after treatment with t-BuLi and pentamethyldiethylenetriamine (PMDTA) in the presence of residual olefin monomers afforded PO-block-PSs. Organolithium species that might be generated in the pot of t-BuLi, PMDTA, and olefin monomers, i.e., [Me2NCH2CH2N(Me)CH2CH2N(Me)CH2Li, Me2NCH2CH2N(Me)Li(PMDTA), pentylallyl-Li(PMDTA)], as well as PhLi(PMDTA), were screened as initiators to grow PS chains from (1-hexyl)2Zn, as well as from (polyolefinyl)2Zn. Pentylallyl-Li(PMDTA) was the best initiator. The Mn values increased substantially after the styrene polymerization with some generation of homo-PSs (27-29%). The Mn values of the extracted homo-PS suggested that PS chains were grown mainly from polyolefinyl groups in [(polyolefinyl)2(pentylallyl)Zn]-[Li(PMDTA)]+ formed by pentylallyl-Li(PMDTA) acting onto (polyolefinyl)2Zn.
Keywords: Chain transfer polymerization; Dialkylzinc; Organolithium species; Organolithiums; Polystyrene block copolymers; Polystyrene chains; Selective removal; Styrene polymerization; Block copolymer; Coordinative chain transfer polymerization; Dialkylzinc; Initiator; Organolithium; Polyolefin; Polystyrene